EP899 Diagnostic value of postoperative platelet-to-white blood cell ratio (PC/WCC) after splenectomy in advanced ovarian cancer patients. (1st November 2019) - Lathouras, K; Panagakis, G; Bowden, S; Saliaris, K; Saso, S; Haidopoulos, D; Fotopoulou, C
Abstract : Introduction/Background: Splenectomy is an established procedure in primary and relapsed cytoreduction in order to achieve total macroscopic tumor clearness in ovarian cancer (OC).Reactive, splenectomy-induced thrombocytosis and leucocytosis may obscure the early diagnosis of post-operative infection or sepsis.In trauma patients after splenectomy, a platelet- to white cell count ratio (PC/WCC) of <20 has been demonstrated to reliably differentiate post-operative sepsis from transient physiological responses to splenectomy.However, this has never been assessed in OC surgery. Methodology: All consecutive OC-patients who underwent splenectomy as part of their cytoreduction between 01/2013 and 10/2018 in two large European gynaecological cancer centres were retrospectively evaluated.Main outcome measures were WCC, PC and PC/WCC-ratio on post-operative days 1, 5&7 and correlated with surgical outcome and morbidity as per the Clavien-Dindo Classification.A binomial logistic regression was applied to assess the predictive value of day five PC/WCC-ratio, WCC and PC for predicting grade III post-operative sepsis. Results: Ninety-five OC-patients (mean age: 54 years, range:18–75) were identified after primary (73%), interval (5%) and secondary (18%) cytoreductive surgery.Other multivisceral procedures were: bowel resection (74%), diaphragmatic/liver capsule stripping (74%), and distal pancreatectomy (5%). 18% (n=17) developed a grade-III post-operative sepsis (infected group) secondary to anastomotic leak (n=2), pneumonia (n=1), left sub-diaphragmatic collection or intra-abdominal collection (n=3) and septicaemia (n=11). A WCC of more than 15 on day five was significantly predictive of postoperative sepsis (OR=1.32; 95% CI 1.12–1.55; p<0.001). However, PC/WCC-ratio (OR=0.97; 95% CI 0.93–1.021; p=0.085)and PC (OR=1.00; 95% CI 0.99–1.00; p=0.409) failed to show any statistical significant predictive value in differentiating between sepsis and reactive, splenectomy induced changes. Assessing the ability of PC/WCC-ratio on day five to predict post-operative sepsis in ROC curve analysis resulted in an area under the curve of 0.637 (95% CI 0.480–0.796). A PC/WCC-ratio cut-off of 26 achieved a sensitivity of 72% and specificity of 53% in predicting grade III post-operative sepsis. Conclusion: The PC/WCC-ratio after cytoreductive surgery for ovarian cancer with splenectomy does not appear to have the same predictive value in differentiating between sepsis and reactive splenectomy induced changes as observed in trauma splenectomy patients. Disclosure: Nothing to disclose.